Comparison of Evapotranspiration with Pan Evaporation in Pigeonpea (Cajanus cajan L.) at Anand - Patel, K I; Savani, M B; Shekh, A M (Annals of Arid Zone, 2016)
The relationship between the ratio of actual evapotranspiration (ET) and pan evaporation (EP) with the leaf area index (LAI) of pigeon pea (Cojonus cajan cv. GT-lOO) at Anand was studied during 1992 and 1993. The peak values of ET and LAI. during 50% flowering to pod developl11ent stage of the crop. were 8.6 mm per day and 4.74. respectively. The linear relationship between one another was observed at the same til11e (R2 =0.70). The 50% flowering phase of the crop was found to be critical phase of water requirement in pigconpea. The seasonal ET and the water-use efficiency of the crop were 819 mm and 4.1 kg ha-1 mm-1 respectively.